Chiral or not chiral? A case study of the hexanuclear metalloprisms [Cp*6M6 (µ3-tpt-κN)2(µ-C2O4-κO)3]6+ (M = Rh, Ir, tpt = 2,4,6-tri(pyridin-4-yl)-1,3,5-triazine) - Govindaswamy, Padavattan; Linder, David; Lacour, Jerôme; Süss-Fink, Georg; Therrien, Bruno (My University, 2007)
Cationic hexarhodium and hexairidium complexes with a trigonal prismatic architecture have been synthesised in good yield by self-assembly of the dinuclear oxalato-bridged complexes [Cp*2M2 (µ-C2O4-κO)Cl2] (M = Rh; 1: Ir; 2) with 2,4,6-tri(pyridine-4-yl)-1,3,5-triazine (tpt) in the presence of AgO3SCF3. The trigonal prismatic cations [Cp*6Rh6 (µ3-tpt-κN)2(µ-C2O4-κO)3]6+ (3) and [Cp*6Ir6 (µ3-tpt-κN)2 (µ-C2O4-κO)3]6+ (4) have been isolated as their triflate salts. The single-crystal X-ray structure analysis of [3][O3SCF3]6 shows two enantiomers in the racemic crystal (space group C2/c), the chirality being due to a twist of the two tpt units. By contrast, the single-crystal X-ray structure analysis of [4][O3SCF3]6 shows a perfectly eclipsed conformation of the tpt units, so that 4 is not chiral in the crystal state (space group Fd¯3c). However, in solution, enantiodifferentiation in the presence of the chiral anion Δ-BINPHAT is observed by 1H NMR spectrometry not only in the case of 3, but also in the case of 4. This suggests that the iridium derivative 4, which is not chiral in the solid state, adopts chiral conformations in solution.